On fuzzy theory for econometrics - Hung T. Nguyen (2018)
© Springer International Publishing Switzerland 2015.  This paper aims mainly at informing statisticians and econometricians of relevant concepts and methods in fuzzy theory that are useful in addressing economic problems. We emphasize three recent significant contributions of fuzzy theory to economics, namely fuzzy games for capital risk allocations, fuzzy rule bases and compositional rule of inference for causal inference, and a statistical setting for fuzzy data based on continuous lattices.